2009
DOI: 10.1111/j.1399-302x.2009.00514.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular diversity of Archaea in subgingival pockets of periodontitis patients

Abstract: Archaea might be correlated with periodontal diseases. The diversity of Archaea associated with periodontitis was limited. Almost all sequenced amplicons fell into the genus Methanobrevibacter of the Euryarcheota phylum. M. oralis-like species was the predominant but non-exclusive archaeon in the subgingival dental plaque of patients with periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
3
16

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 24 publications
2
64
3
16
Order By: Relevance
“…Total bacterial control indicated that for a C T value of Ͼ35.5, M. oralis detection was not interpretable. Based on these controls, the detection of M. oralis DNA in healthy individuals (C T Յ 35.5) was possible, in contrast to findings of previous studies (12,13,17,18), and a significant correlation was observed between the M. oralis load and periodontitis severity.…”
contrasting
confidence: 52%
See 2 more Smart Citations
“…Total bacterial control indicated that for a C T value of Ͼ35.5, M. oralis detection was not interpretable. Based on these controls, the detection of M. oralis DNA in healthy individuals (C T Յ 35.5) was possible, in contrast to findings of previous studies (12,13,17,18), and a significant correlation was observed between the M. oralis load and periodontitis severity.…”
contrasting
confidence: 52%
“…PCR systems previously used to detect methanogens in the subgingival plaque (6,8,12,13) were not completely specific for M. oralis. Indeed, other methanogens, including Methanobrevibacter smithii (14), Methanosphaera stadtmanae (6), Methanobacterium curvum/Methanobacterium congolense, and Methano-sarcina mazeii (15,16), have been detected in this situation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…periodontal disease. 20 Sixteen studies were selected [8][9][10][11][12][13][14][15]23,[26][27][28][29][30][31] and Methanobrevibacter, Methanosphaera, Methanosarcina, Thermoplasmata and Methanobacterium were considered the five most common genera of methanogenic Archaea present in the subgingival biofilm. In addition, the pooled prevalence of these studies showed that M. oralis was detected in 41% of the periodontitis subjects in comparison with only 6% of the periodontally healthy subjects (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, as a function of progressing disease, increasing numbers of Archaea (including Methanobrevibacter oralis) can be isolated from subgingival pockets. Despite the lack of any direct cause-effect in vivo studies assessing the role of Archaea in periodontitis, strikingly, these organisms have never been found in the subgingival microflora of healthy individuals or at healthy sites in patients with periodontitis (115,116). The difference between the onsets of chronic and localized aggressive forms of periodontitis is unclear at this time but is thought to result from a host genetic predisposition to colonization, a hyperaggressive immune response to oral bacteria involving increased levels of polymorphonuclear infiltrate, differences mediated by the microbial composition itself, or a combination of these effectors (44,58,84).…”
Section: Diseases Of the Oral Cavitymentioning
confidence: 99%